Comparison of nutrient concentrations in leaves of five plants. (20th January 2017) - Shtangeeva, Irina; Tesfalidet, Solomon; Lövgren, Lars
ABSTRACT: The paper describes investigation on bioaccumulation of mineral elements and identification of plants based on the concentrations of the elements in the plant leaves. Five native plant species ( Elytrigia repens, Plantago major, Urtica dioica, Chelidonium majus, and Taraxacum officinale ) were studied. To exclude the effects from different growth conditions and developmental stages, the plants were collected simultaneously from the same site (park in St. Petersburg, Russia). It was found that for all plants high concentrations of potassium, sodium, phosphorus and magnesium (K, Na, P, and Mg) were typical, while concentrations of zinc (Zn) and copper (Cu) were the lowest. The most significant difference was found between concentrations of elements in monocots and eudicots. Among other species, T. officinale had the highest concentrations of almost all elements. Excellent separation of the plants into different groups which was due to different element concentrations in the plant leaves was demonstrated.